2021
DOI: 10.3847/1538-4357/abca8e
|View full text |Cite
|
Sign up to set email alerts
|

s-processing in AGB Stars Revisited. III. Neutron Captures from MHD Mixing at Different Metallicities and Observational Constraints

Abstract: We present post-process neutron-capture computations for Asymptotic Giant Branch (AGB) stars of 1.5–3 M ⊙ and metallicities −1.3 ≤ [Fe/H] ≤ 0.1. The reference stellar models are computed with the FRANEC code, using the Schwarzschild's criterion for convection; our motivations for this choice are outlined. We assume that MHD processes induce the penetration of protons below the convective boundary, when the Third Dredge Up occurs. There, the 13C n-source can subsequently operate, merging its e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 134 publications
2
77
0
Order By: Relevance
“…r p can be identified from the critical toroidal B ϕ necessary for the onset of magnetic buoyancy instabilities (Vescovi et al 2020). k is the exponent quantifying the density decline, being ρ(r) ∝ r k , in the He-rich radiative layers below the convective envelope during a TDU, and it is typically lower than −3 (see also Busso et al 2021). The identification of the critical field necessary for the occurrence of instabilities by magnetic buoyancy allows identifying the corresponding radial position r p from which magnetic structures arise.…”
Section: Stellar Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…r p can be identified from the critical toroidal B ϕ necessary for the onset of magnetic buoyancy instabilities (Vescovi et al 2020). k is the exponent quantifying the density decline, being ρ(r) ∝ r k , in the He-rich radiative layers below the convective envelope during a TDU, and it is typically lower than −3 (see also Busso et al 2021). The identification of the critical field necessary for the occurrence of instabilities by magnetic buoyancy allows identifying the corresponding radial position r p from which magnetic structures arise.…”
Section: Stellar Modelsmentioning
confidence: 99%
“…Post-process neutron-capture models for AGB stars in which the formation of the required 13 C reservoir is ascribed to mixing induced by magnetic buoyancy were shown to be able to account for the solar distributions of s-only isotopes (Trippella et al 2016), isotopic ratios of s-elements measured in presolar SiC grains (Palmerini et al 2018), and for a large part of the abundance observations in evolved low-mass stars (Busso et al 2021). The theory of mixing triggered by magnetic buoyancy developed by Nucci & Busso (2014) was used for this.…”
Section: Introductionmentioning
confidence: 99%
“…This causes the s-path to proceed towards 182 W and the 182 Hf production to be low. However, the radiogenic contribution of 182 Hf occurring at the end of the TP-AGB phase is important to explain the solar abundance of 182 W. Present AGB estimations for the s-process main component can account for 65-70% of solar 182 W [17,38], while its r-process contribution is well justified by the Galactic enrichment of r-process elements [39]. However, Lugaro et al [40] have pointed out that the present AGB contributions to 182 Hf and 182 W may have so far been underestimated.…”
Section: Resultsmentioning
confidence: 97%
“…More recently, the suggestion that stellar magnetic activity might be responsible for the formation of the 13 C pocket through mixing induced by magnetic buoyancy has been proposed [14,15]. Post-process calculations of such a 13 C reservoir have shown to be able to reproduce the distribution of s-elements in the solar main component [15], heavy-element isotopic compositions of presolar grains [16], and most of n-capture elements abundances observed in Ba-stars and post-AGB stars [17]. These studies have been confirmed by numerical simulations of the formation of a magnetically-buoyancy-induced 13 C pocket in a new series of FRUITY stellar evolutionary models [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, its luminosity is too low to be self-enriched in s−process elements because this should only happen when the star is in the phase of the thermal pulses (TP-AGB, see e.g. Busso et al 1999 andBusso et al 2021 andreferences therein). Furthermore, the overabundance of Eu precludes this interpretation because Eu is a pure r−process element.…”
Section: Rubidiummentioning
confidence: 99%